30th AIAA Applied Aerodynamics Conference 2012
DOI: 10.2514/6.2012-3203
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach to High-Altitude, Long-Endurance Stationkeeping

Abstract: A new concept for achieving high-altitude, long-endurance (HALE) flight is proposed and evaluated, which features two unmanned aerial vehicles (UAVs) connected via a long tether which effectively sail backand-forth using stratospheric wind velocity gradients. The potential of a baseline configuration to stationkeep (i.e., stay within a prescribed radius above a specific ground site) based on measured steady wind profiles is predicted analytically based on yearly sets of bi-daily wind profiles, and using a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…where e is the energy conversion efficiency of solar cell. Equations (9) to (11) imply that the energy supply rate relies mainly on three parameters: weight, solar spectral irradiance, and energy conversion rate of solar cell. Previous researches 57,58 have found that most of flying animals have a flapping range of 120 to keep good aerodynamic performance.…”
Section: Energy Analysis Of a Solar Cell Fwmavmentioning
confidence: 99%
See 1 more Smart Citation
“…where e is the energy conversion efficiency of solar cell. Equations (9) to (11) imply that the energy supply rate relies mainly on three parameters: weight, solar spectral irradiance, and energy conversion rate of solar cell. Previous researches 57,58 have found that most of flying animals have a flapping range of 120 to keep good aerodynamic performance.…”
Section: Energy Analysis Of a Solar Cell Fwmavmentioning
confidence: 99%
“…8 In 2010, DARPA funded the Boeing Solar Eagle project, which aims at staying aloft for up to five years at altitudes above 60,000 feet. 9 Although these given examples are all fixed wing versions, they show us a great potential that solar cell could be an effective means to increase flight duration of aircraft vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…The Global SUAV Market 2020-2024 report states that the SUAV market is expected to grow by around USD 500 million by 2024 and has the potential to reach USD 3800 million by the end of 2033 [9]. In addition, numerous small private firms and large tech and aviation companies have been actively engaged in the SUAV market for a long time to develop state-of-the-art SUAVs, for example, Boeing, Google, and Airbus [10,11]. Equipping proper solar panels on UAVs provides them with the functionality to charge themselves while in the sunshine.…”
Section: Introductionmentioning
confidence: 99%
“…These include but are not limited to Solar Impulse I and II, Facebook's UAS-based Internet platform, National Aeronautics and Space Administration's (NASA) Pathfinder and AeroVironment's Helios aircraft, and Boeing's SolarEagle. [51][52][53][54] The advantages of these systems are to provide station keeping 51 and to reduce the environmental impact. 54 Gathering solar energy via photovoltaics can be more efficient than other energy harvesting technologies, if they are used in conjunction with optimized energy transfer techniques, such as maximum power point tracking (MPPT).…”
Section: Introductionmentioning
confidence: 99%